Gambaran fisiologis domba di Desa oesao Kecamatan Kupang Timur Kabupaten Kupang - Carlo YR Hina; Yohanes T. R. M. R Simarmata; Meity M. Laut (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Sheep is encountered in tropical area because can life good in extreme environment conditions. Sheep is a hot blood animal because can maintain body temperature in specified range. High temperature of envorenment cause stress of animal, because heat regulation system is not balanced with environment. Animals That stress Due Environment Temperature Heat, causing changes in physiology behaviour what can be measured from changes in rectal temperature, respiratory frequency and heart rate. The difference environmental temperature in each place causes a difference of body temperature in animal. Because of that, it’s important to having the optimal temperature animal on that place, to keep the growth and productivity functions. Kupang regency is in the semi arid area with high environment temperature and the low rainfall especially in oesao village. Because of that, and there’s not data of sheep physiological in Kupang district, Researchers Want to know the normal physiological of sheep in Oesao Village District of East Kupang, Kupang. The measured parameter are body temperature, respiration and pulse. This research uses as much as 24 fat tail sheep. Sample are grouped based on age. Young group with age <1 years, and adult group with age >1 years. The result showed that Rectal temperature fat tail sheep in the village Oesao on morning is 39,0ºC to 39,8ºC and day is 39,9ºC to 39,3ºC. The mean frequency of respiration on morning is 33 x / min to 38 x / min days 35 x / min to 39 x / min. The mean heart rate is on the morning is 78 x / min to 81 x / min and day 80 x / min to 82 x / min. it is concluded that the value of the physiological fat tail sheep in Oesao is on normal range.